2010
DOI: 10.1111/j.1471-4159.2010.06888.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered microglial copper homeostasis in a mouse model of Alzheimer’s disease

Abstract: J. Neurochem. (2010) 114, 1630–1638. Abstract Alzheimer’s disease (AD) is characterized by progressive neurodegeneration associated with the aggregation and deposition of β‐amyloid (Aβ40 and Aβ42) peptide in senile plaques. Recent studies suggest that copper may play an important role in AD pathology. Copper concentrations are elevated in amyloid plaques and copper binds with high affinity to the Aβ peptide and promotes Aβ oligomerization and neurotoxicity. Despite this connection between copper and AD, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 61 publications
(108 reference statements)
1
69
0
Order By: Relevance
“…6D) but only a small decrease in 64 Cu uptake (0.93 ± 0.30 vs. 1.15 ± 0.53 %ID/g, P = 0.33) as shown in Figure 5. Our results suggest that increased uptake of 64 Cu in the traumatized brain tissues is likely caused by a combination of increased copper uptake by activated microglial cells (16), copper/zinc superoxide dismutase (17), and other copper transporters or chaperones (12). In view of the potential difference in neuroinflammation between the time of PET/CT and the time of postmortem brain tissue harvesting, 5 d after PET/CT, it would be ideal to correlate uptake and neuroinflammation with PET/CT using 64 CuCl 2 and other tracers specific for biomarkers of neuroinflammation simultaneously (31,32).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…6D) but only a small decrease in 64 Cu uptake (0.93 ± 0.30 vs. 1.15 ± 0.53 %ID/g, P = 0.33) as shown in Figure 5. Our results suggest that increased uptake of 64 Cu in the traumatized brain tissues is likely caused by a combination of increased copper uptake by activated microglial cells (16), copper/zinc superoxide dismutase (17), and other copper transporters or chaperones (12). In view of the potential difference in neuroinflammation between the time of PET/CT and the time of postmortem brain tissue harvesting, 5 d after PET/CT, it would be ideal to correlate uptake and neuroinflammation with PET/CT using 64 CuCl 2 and other tracers specific for biomarkers of neuroinflammation simultaneously (31,32).…”
Section: Discussionmentioning
confidence: 89%
“…The molecular mechanisms by which copper plays a role in wound repair are not fully understood but may be related to induction of vascular endothelial growth factor expression for angiogenesis (15) and to copper-containing molecules serving an essential function in cell proliferation in the wound-healing process. In response to TBI, there may be increased copper uptake by activated microglia secondary to posttraumatic neuroinflammation (16), copper/zinc superoxide dismutase (17), and potentially other copper transporters and chaperones defending oxidative damage (18). …”
mentioning
confidence: 99%
“…It has been suggested that failure of Cu sequestration by microglia clustered around amyloid plaques may precipitate inflammatory conditions and thus exacerbate AD (Zheng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In plants and many microorganisms they have an important role in copper homeostasis and detoxification 23,24 . The two Cu 1 -transporting PIB-ATPases in human are ATP7A and ATP7B, which are of vital importance [25][26][27] ; defects give rise to Menkes' and Wilson's diseases, respectively, whereas upregulation has been associated with Alzheimer's diease 28 and resistance to cancer chemotherapy 29 .…”
mentioning
confidence: 99%